Organizational Communication Between Teacher And Students In Improving Learning Motivation - Soedarsono, Dewi K (Jurnal Sosial Sains dan Komunikasi, 2023)
The aim of the study was to find out the systematic explanation of communication between teachers and students in increasing learning motivation at SDN Gumuruh 8 Bandung City. The research method uses a descriptive-qualitative approach with a qualitative research type, data collection is done through in-depth interviews and informant reporting methods, and data analysis consists of data collection, data reduction, data presentation, and inference. will be used. The results of the study show that organized communication between teachers and students motivates learning through direct (face to face) and indirect (through the media) communication at SDN Gumuruh 8 Bandung City. The supporting element in organizational communication is the existence of effective interaction with students which motivates learning. This includes, for example, developing lesson plans, appropriate instructional media, overcoming difficulties faced by students during the learning process, and carrying out work assessments to then improve the communication process between teachers and students.